The Effectiveness Of Audiovisual Narrative Story The Boy Who Cried Wolf On Students’ Listening Comprehension Skills At Smk Gondang - Farid Akhdan Hafidz (LPPM Universitas Pekalongan, 2026)
This study investigates the effectiveness of using an audiovisual narrative story entitled 'The Boy Who Cried Wolf' to improve students’ listening comprehension skills at SMK Gondang. A quasi-experimental design was employed involving an experimental group and a control group. The experimental group was taught using audiovisual narrative media, while the control group received conventional listening instruction. Data were collected through pre-tests and post-tests and analyzed using an independent samples t-test. The findings revealed that students taught through audiovisual narrative stories showed significantly higher improvement in listening comprehension compared to those taught through conventional methods. The results indicate that audiovisual narrative media are effective in enhancing students’ listening comprehension skills.